1998
DOI: 10.1002/(sici)1097-4628(19980228)67:9<1573::aid-app9>3.3.co;2-t
|View full text |Cite
|
Sign up to set email alerts
|

Modeling of industrial nylon‐6,6 polycondensation process in a twin‐screw extruder reactor. I. phenomenological model and parameter adjusting

Abstract: This article describes a mathematical model for the finishing stage of nylon-6,6 polycondensation in a twin-screw extruder reactor. In the model, the extruder is conceptually divided into two regions. The first one is the partially filled degassing zone, which is operated under low pressure and where the evaporation of water from the polymer takes place. The rate of evaporation is considered to depend on an overall mass transfer coefficient and is limited by the water-polymer physical equilibrium. In the secon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
24
0

Year Published

2003
2003
2019
2019

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(24 citation statements)
references
References 1 publication
0
24
0
Order By: Relevance
“…When nylon 6,6 is heated beyond 265 °C, the concentration of these cyclopentanone end groups (denoted by S in reactions R9 and R10) tends to increase over time, accompanied by an increase in [ A ] and a corresponding decrease in [ C ] . Reactions R9 and R10 were included in nylon 6,6 modeling studies by Steppan et al., Giudici et al., and Schaffer et al., to account for end‐group concentration changes in their data and models …”
Section: Reaction Mechanism and Literature Reviewmentioning
confidence: 99%
“…When nylon 6,6 is heated beyond 265 °C, the concentration of these cyclopentanone end groups (denoted by S in reactions R9 and R10) tends to increase over time, accompanied by an increase in [ A ] and a corresponding decrease in [ C ] . Reactions R9 and R10 were included in nylon 6,6 modeling studies by Steppan et al., Giudici et al., and Schaffer et al., to account for end‐group concentration changes in their data and models …”
Section: Reaction Mechanism and Literature Reviewmentioning
confidence: 99%
“…In Equation (9), we have assumed that the degassing process occurs at the melt-gaseous phase interface 3,40 , ! c i W ,eq being the melt equilibrium water concentration corresponding to the vent pressure !…”
Section: Model Equationsmentioning
confidence: 99%
“…Mass transfer of volatile species during nylon 6 and nylon 6,6 polymerization has been considered in previous modeling studies. [37,38,40,46,48,[53][54][55][56][59][60][61][62][63][64][65][66][67][68][69][70][71] A literature review by Schaffer et al [71] found that typical values of the lumped mass-transfer coefficient k w A s , where A s is the surface area, range from a low value of 8 h -1 for a labscale reactor system with no nitrogen bubbling or stirring to a high value of 324 h -1 obtained in a two-phase twinscrew extruder reactor. Appropriate values of k w A s for use in mathematical models depend on the type and size of reactor and agitator, the agitation speed, reactor geometry and physical properties of the liquid phase.…”
Section: Introductionmentioning
confidence: 99%
“…Mass transfer of volatile species during nylon 6 and nylon 6,6 polymerization has been considered in previous modeling studies . A literature review by Schaffer et al found that typical values of the lumped mass‐transfer coefficient k w A s , where A s is the surface area, range from a low value of 8 h ‐1 for a lab‐scale reactor system with no nitrogen bubbling or stirring to a high value of 324 h ‐1 obtained in a two‐phase twin‐screw extruder reactor.…”
Section: Introductionmentioning
confidence: 99%